2018
DOI: 10.1111/jphd.12299
|View full text |Cite
|
Sign up to set email alerts
|

Association of food insecurity with early childhood caries

Abstract: Objectives The aim of this study was to examine the association of food insecurity on the prevalence of dental caries in preschool children. Methods Eighty‐two children, aged 12‐71 months old, from the Marquette University School of Dentistry Community South Clinic and their caregivers participated in this cross‐sectional study. Following informed consent, parents completed the validated six‐item US Department of Agriculture food insecurity questionnaire and questions regarding demographic information and fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 13 publications
3
44
0
Order By: Relevance
“…Other barriers are a lack of oral health awareness, social determinants of health and caregiver hygiene behaviours for children aged less than 72 months. 5,7 Increasing caregivers' awareness can help modify behaviours known to contribute to early childhood caries. 8,9 The Healthy Smile Happy Child (HSHC) initiative has taken a community development approach to promoting young children's oral health.…”
Section: Introductionmentioning
confidence: 99%
“…Other barriers are a lack of oral health awareness, social determinants of health and caregiver hygiene behaviours for children aged less than 72 months. 5,7 Increasing caregivers' awareness can help modify behaviours known to contribute to early childhood caries. 8,9 The Healthy Smile Happy Child (HSHC) initiative has taken a community development approach to promoting young children's oral health.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this public health issue does not bypass families with particularly young children, given that more than 16 % of households with children under the age of 6 years experienced food insecurity in 2017 (3) . Research to date has linked household food insecurity to myriad deleterious health outcomes among young children, including elevated BMI/obesity (4,5) , asthma (6) and dental caries (7) . The impact of household food insecurity, however, extends beyond these physical health challenges to diverse psychological, academic and behavioural challenges, including among very young children (8)(9)(10)(11)(12) .…”
mentioning
confidence: 99%
“…The higher prevalence of overweight in countries with higher estimates of ECC in 0-2-year-olds may reflect the findings by El Tantawi et al [26] who reported a higher prevalence of ECC in countries with greater economic growth. ECC and overweight/obesity share common risk factorshigh frequency and quantity of free sugar consumption [36], food insecurity [37,38], low socioeconomic status [39][40][41], residence in urban slums [42,43] and rural areas [44,45]. Growing economies are most likely to be undergoing nutrition transitions from traditional diets to low quality, processed, high-sugar, high-fat, carbohydrate-dense food and beverages that are poor in micronutrients [46,47], which predisposes to overweight and high ECC prevalence.…”
Section: Discussionmentioning
confidence: 99%